Digital Innovations in the Hotel Business: Analysis of Foreign Experience - Shirin Yakubovna Abdusaidova (International Journal on Economics, Finance and Sustainable Development, 2021)
The purpose of this article is to describe and evaluate new hotel service innovations that deserve to be considered for implementation in hotel businesses. The paper is timely since hotel buildings are becoming increasingly interested in the development and deployment of new technologies, as well as the problems of improving the quality and competitiveness of services at hotel enterprises, the solution of which can be innovation. This article describes digital innovation advances that can be applied to hospitality businesses. The article also provides an aggregated calculation of the income and expenses of a hotel project using innovative technologies. In conclusion, it is said that innovations can and should be used to solve problems of attracting new and retaining existing customers, due to timely response to customer needs.